Chronic alcoholic skeletal muscle myopathy: a clinical, histological and biochemical assessment of muscle lipid. - Sunnasy, D (1983)
Muscle biopsy samples were analysed from five control subjects, four patients with mild to moderate fibre atrophy and four patients with severe atrophy. Patchy increase in lipid was noted with oil red O staining but there was no consistent association of lipid with selective fibre types. Ultrastructural studies demonstrated lipid droplets both subjacent to the sarcolemma and between fibrils. Quantitative analysis showed that the increased lipid was solely due to excess triglyceride. GLC analysis of free and esterified acids was performed. The profiles were essentially similar for the phospholipid and free fatty acid fractions. The triglyceride fraction showed a decrease of myristate, stearate and linoleate with an increase in oleate and arachidate in the alcoholic tissue compared with control. The cholesteryl ester fraction showed an increase in palmitate with a decrease in stearate and oleate in the alcoholic muscle. The accumulation of lipid correlated with mean daily alcohol consumption but not with degree of atrophy suggesting that the two processes probably had different pathogenic mechanisms.